A Comparison of Dose Metrics to Predict Local Tumor Control for Photofrin‐mediated Photodynamic Therapy. (22nd February 2017) - Qiu, Haixia; Kim, Michele M.; Penjweini, Rozhin; Finlay, Jarod C.; Busch, Theresa M.; Wang, Tianhao; Guo, Wensheng; Cengel, Keith A.; Simone, Charles B.; Glatstein, Eli; Zhu, Timothy C.
Abstract: This preclinical study examines light fluence, photodynamic therapy (PDT) dose and "apparent reacted singlet oxygen, " [ 1 O2 ]rx, to predict local control rate (LCR) for Photofrin‐mediated PDT of radiation‐induced fibrosarcoma (RIF) tumors. Mice bearing RIF tumors were treated with in‐air fluences (50–250 J cm −2 ) and in‐air fluence rates (50–150 mW cm −2 ) at Photofrin dosages of 5 and 15 mg kg −1 and a drug‐light interval of 24 h using a 630‐nm, 1‐cm‐diameter collimated laser. A macroscopic model was used to calculate [ 1 O2 ]rx and PDT dose based on in vivo explicit dosimetry of the drug concentration, light fluence and tissue optical properties. PDT dose and [ 1 O2 ]rx were defined as a temporal integral of drug concentration and fluence rate, and singlet oxygen concentration consumed divided by the singlet oxygen lifetime, respectively. LCR was stratified for different dose metrics for 74 mice (66 + 8 control). Complete tumor control at 14 days was observed for [ 1 O2 ]rx ≥ 1.1 mm or PDT dose ≥1200 μm J cm −2 but cannot be predicted with fluence alone. LCR increases with increasing [ 1 O2 ]rx and PDT dose but is not well correlated with fluence. Comparing dosimetric quantities, [ 1 O2 ]rx outperformed both PDT dose and fluence in predicting tumor response and correlating with LCR. Abstract : This preclinical study examines light fluence, photodynamic therapy (PDT) dose and "apparent reacted singlet oxygen, " [ 1 O2 ]rx, to predict local control rate (LCR) for Photofrin‐mediated PDT of radiation‐induced fibrosarcoma (RIF) tumors. LCR was stratified for different dose metrics for 74 mice (66 + 8 control). Complete tumor control at 14 days was observed for [ 1 O2 ]rx ≥ 1.1 mm or PDT dose ≥1200 µm J cm −2 but cannot be predicted with fluence alone. LCR increases with increasing [ 1 O2 ]rx and PDT dose but is not well correlated with fluence. Comparing dosimetric quantities, [ 1 O2 ]rx outperformed both PDT dose and fluence in predicting tumor response and correlating with LCR.